2014
DOI: 10.1016/j.ddtec.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological correction of misfolding of ABC proteins

Abstract: The endoplasmic reticulum (ER) quality control system distinguishes between correctly and incorrectly folded proteins to prevent processing of aberrantly folded conformations along the secretory pathway. Non-synonymous mutations can lead to misfolding of ABC proteins and associated disease phenotypes. Specific phenotypes may at least partially be corrected by small molecules, so-called pharmacological chaperones. Screening for folding correctors is expected to open an avenue for treatment of diseases such as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…It has been hypothesized that if the cellular environment can be altered, the CFTR protein defect may be bypassed. One of the ways to approach this is by improving proteostasis in CF cells [4244]. Proteostasis improvement helps to re-establish the plasma membrane localization of CFTR.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that if the cellular environment can be altered, the CFTR protein defect may be bypassed. One of the ways to approach this is by improving proteostasis in CF cells [4244]. Proteostasis improvement helps to re-establish the plasma membrane localization of CFTR.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, reports have surfaced regarding pharmacological approaches to correcting misfolding of a subfraction of proteins in the secretory pathway, including mutant enzymes, receptors, transporters, and ion channels (38), such as the cystic fibrosis transmembrane regulator (39), ATP-binding cassette transporters (40), gonadotropin-releasing hormone receptor (41), superoxide dismutase 1 (42), lysosomal enzymes like β-glucosidase (43), and others. Pharmacotherapies are beginning to be reported that can ameliorate ER stress in pancreatic β-cells as well (4447); however, no pharmacotherapies that specifically help correct proinsulin misfolding in the ER have yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with specific mutations in ABCB11 (primarily miss-sense mutations), the basic transporter defect may be (partially) overcome by chaperones/small molecule strategies (e.g., 4-phenybutyrate and glycerol phenylbutyrate) that promote protein folding and enhance the functional expression of transport proteins in the liver [104]. Inhibition of intestinal bile acid absorption is being investigated as an alternative approach to treat these diseases.…”
Section: Progressive Familial Intrahepatic Cholestasis (Pfic)mentioning
confidence: 99%